Collaborative Governance Kebijakan Kemandirian Pangan untuk Penanggulangan Kemiskinan di Provinsi Sumatera Selatan - Febriansyah, Muhammad Firdaus; Nadjib, Abdul; Prabujaya, Sena Putra (Mahesa Research Center, 2024)
This study aims to examine the application of Collaborative Governance in poverty alleviation efforts through food self-sufficiency policies in South Sumatra Province. The focus of the research is on actor collaboration within food self-sufficiency policies as a strategy to reduce poverty. This study uses Weber’s theory, which includes vertical, horizontal, and partnership dimensions. Data were collected through public documentation and online videotapes and analyzed qualitatively. The study concludes that the vertical dimension has been met, as there is a legal basis for food self-sufficiency policies; the horizontal dimension is evident through the involvement of non-governmental actors, such as Bank Sumsel Babel; and the partnership dimension is also fulfilled due to binding negotiations between actors, positive partner perspectives, as well as the availability of human resources, political support, and financial resources for policy implementation. However, there are still challenges related to trust levels. Therefore, ongoing socialization of food self-sufficiency policies is needed to build trust among partners. Once this is addressed, food self-sufficiency policies could likely become a viable solution for poverty alleviation across Indonesia.